Os sítios arqueológicos Novo Império 1 e 2 da fazenda experimental da UFOPA: um estudo de distribuição espacial dos vestígios - ALVES, Gilvandro Flávio de Sousa (Universidade Federal do Oeste do Pará, 2024)
The Experimental Farm located in the Santareno plateau region is used by several courses at the Federal University of West Pará (UFOPA) and is intended for the practical teaching of several courses, including the teaching activities of the Archeology Course. From the field practices started in 2016, two large concentrations (Sítios Novo Império 1 and Novo Império 2) of archaeological material, especially ceramic fragments, were found in the context of terra preta de Índio (TPI). In this way, we seek to understand the distribution of archaeological remains found at the Novo Império 1 and 2 sites through the application of spatial analysis of the concentrations of ceramic material on maps, cross-referencing data through tables and graphs. Since there are still few studies carried out on the Santareno plateau compared to the urban part of the city, in the areas of the Porto and Aldeia sites, understanding these sites is important to aggregate relevant information for the construction of the pre-colonial past of the city as a whole. Thus, from the analyzes carried out, we were able to contribute to thinking about the relationships that these different occupations could have in the past.